Teaching police ethics: An experiential model - Miller, Larry S. (American journal of criminal justice, 1985)
Attempts have been made in recent years to decrease police misconduct and improve police performance in areas of ethical decision-making. One attempt has been to provide ethics instruction to police officers at training academies and in-service training sessions. Experiential case studies have been used to help students apply theoretical concepts to practical situations. An evaluation of the experiential teaching model for police ethics was made in a quasiexperimental research design with two groups of police officers. The results supported the experiential approach for teaching police ethics. Police officers were found to better differentiate between ethical and unethical conduct in both an idealistic and realistic manner.